Partial substitution of nitrate by chloride in fertigation recipes allows for lower nitrate input in hydroponic lettuce crops - Neocleous, Damianos; Savvas, Dimitrios; Giannothanasis, Evangelos; Ntatsi, Georgia (Frontiers in Plant Science, 2024)
The management of nitrogen (N) fertilization is of fundamental importance in hydroponics. To reduce the supply of nitrate (NO3 -) in fertigation recipes for Batavia lettuce crops grown in closed hydroponics, partial replacement of nitrate by chloride (NO3 -/Cl -) at different ratios but with the same equivalent sum was experimentally tested. The experiment included four nutritional treatments in the replenishment nutrient solution, particularly T1; 0.7 mM Cl -/19 mM NO3 -, T2; 2 mM Cl -/17.7 mM NO3 -, T3; 4 mM Cl -/15.7 mM NO3 -and T4; 6 mM Cl -/13.7 mM NO3 -. The results showed that reducing nitrate supply combined with equivalent increase in chloride application gradually reduced the gap between nitrate input and nitrogen uptake concentrations, with the smallest differences occurring in T4 treatment, which reduced the nitrate concentration in the drainage by 50%. The tested treatments led to very small variations in plant water uptake, production of fresh biomass and nutritional quality, which is justified by the proper functioning of key physiological mechanisms, such as stomatal conductance, which was followed by an increased efficiency of nitrogen use up to 25% (kg fresh biomass kg -1 N supply). The steady level of C/N ratio in the plant tissue irrespective of NO3 -/Cl -supply ratio points to sufficiency in photosynthetic products and adequacy in the supply of nitrogen, although leaf Cl -content increased up to 19.6 mg g -1 dry weight in the lowest NO3 -/Cl -treatment. Nutrient uptake concentrations were determined as follows: 13.4 (N), 1.72 (P), 10.2 (K), 3.13 (Ca), 0.86 (Mg, mmol L - 1 ), 27.8 (Fe), 5.63 (Mn), 5.45 (Zn) and 0.72 (Cu, μmol L -1 ). This study suggests that replacing 30% of NO3 -supply with Cl -in fertigation recipes for hydroponic lettuce crops reduces leaf nitrate content without affecting physiological processes, growth, and quality, verifying in parallel the role of chloride as a beneficial macronutrient. Finally, a relationship between Cl -uptake and its concentration in the root zone solution was established enabling the simulation of chloride to water consumption.